Improving Capacity for Stabilization and Reconstruction Operations - Bensahel, Nora (RAND Corporation, 2009)
U.S. experiences in Iraq and Afghanistan have demonstrated that improving U.S. capacity for stabilization and reconstruction operations is critical to national security. The authors recommend building civilian rather than military capacity, realigning and reforming existing agencies, and funding promising programs. They also suggest improvements to deployable police capacity, crisis-management processes, and guidance and funding.